2019
DOI: 10.1186/s13063-018-3164-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect and neurophysiological mechanism of acupuncture in patients with chronic sciatica: protocol for a randomized, patient-assessor blind, sham-controlled clinical trial

Abstract: BackgroundSciatica is a relatively frequent illness that easily becomes a chronic and relapsing condition. Although numerous systematic reviews have analyzed various therapies for sciatica, the validity of their included studies is limited. Considering the limitations of conventional treatment options for sciatica, acupuncture is a possible option; however, evidence supporting its efficacy and mechanism in patients with sciatica is lacking. The aim of this proposed protocol is to investigate the effect and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“… 17 , 57 These acupoints were selected by a process of consensus with doctors of Korea medicine who all specialized in Rehabilitation Medicine of Korean Medicine on the basis of a literature review regarding acupuncture for low back pain and sciatica. 31 For the acupuncture treatments, mice were mildly immobilized, and a sterilized acupuncture needle (8 mm in length and 0.18 mm in diameter; Haenglim-seoweon Acuneedle Co, Gyeonggi-Do, South Korea) was inserted bilaterally to a depth of 3 mm and turned bidirectionally for 30 seconds (twice per second; one 180° clockwise rotation and one 180° counterclockwise rotation) using the fingers. Using hematoxylin and eosin staining, we observed that there were needle tracts around the acupunctured sites regardless of acupoint but no tissue damage and/or inflammatory response (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 57 These acupoints were selected by a process of consensus with doctors of Korea medicine who all specialized in Rehabilitation Medicine of Korean Medicine on the basis of a literature review regarding acupuncture for low back pain and sciatica. 31 For the acupuncture treatments, mice were mildly immobilized, and a sterilized acupuncture needle (8 mm in length and 0.18 mm in diameter; Haenglim-seoweon Acuneedle Co, Gyeonggi-Do, South Korea) was inserted bilaterally to a depth of 3 mm and turned bidirectionally for 30 seconds (twice per second; one 180° clockwise rotation and one 180° counterclockwise rotation) using the fingers. Using hematoxylin and eosin staining, we observed that there were needle tracts around the acupunctured sites regardless of acupoint but no tissue damage and/or inflammatory response (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…These subclasses have both common and divergent acupoints (Kim et al, 2020). A randomized controlled trial, a coping strategy, a questionnaire, Beck's depression inventory, and the State-Trait Anxiety Inventory were used to evaluate the therapeutic effects of acupuncture on chronic sciatica (Kim et al, 2019). In another randomized controlled trial, the feasibility and efficacy of acupuncture for atopic dermatitis (including pruritus) were evaluated using instruments including the Center for Epidemiologic Studies Depression Scale (Kang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The neurophysiological mechanisms of acupuncture analgesia have been recorded and included: opiate and nonopiate pain modulation, hippocampal nitric oxide synthase activity, and the expression of various mediators of neurologic inflammation have been documented as well. (10).…”
Section: Discussionmentioning
confidence: 99%